Thermal conductivity and Thermal properties enhancement of Paraffin/Titanium Oxide based Nano enhanced Phase change materials for Energy storage - Ali Laghari, Imtiaz; Samykano, Mahendran; Pandey, A.K; Said, Zafar; Kadirgma, K.; Tyagi, V.V. (IEEE Xplore, 2022)
The Latent heat storage (LHS) based on phase change materials (PCMs) has a critical part to demonstration in preserving and efficiently utilizing energy, resolving demand-supply mismatches, and boosting the efficiency of energy systems. However, they have a low thermal performance inherent in it because the low thermal conductivity (TC) of PCMs. Paraffin organic PCMs have several advantages such as higher LHS, nontoxic, abundant in nature and inexpensive, whereas TiO2 nanoparticle is type of hydrophilic group having tendency to improve TC. In this research TiO2 in different concentration (0.1, 0.5, 1, and 2 wt percent) with surfactant sodium dodecyl benzene sulphonate (SDBS) added into Paraffin RT44 HC PCM using two step techniques, and the thermophysical properties were broadly discussed. Thermogravimetric analyzer (TGA), Fourier transform infrared spectroscopy (FT-IR) and Thermal property analyzer (TEMPOS) were used for the characterization of prepared composite nano-enhanced phase change materials (NePCM). Additionally, the effect of nanoparticles on TC was investigated. The highest TC was obtained with PW/TiO2-1.0 by an increment of 86.36% as related with base PW. The FTIR spectrum of the composite PW/TiO2 confirmed no interaction between PW and TiO2, resulting in a more chemical stable composite. The addition of TiO2 to PW enhance the degrading temperature 10 C by making it more thermal stable. Grounded on the results it can be concluded that the developed composite is suitable for thermal energy storage (TES), photovoltaic thermal (PVT) systems, and hot water applications.